1988
DOI: 10.1021/ja00215a044
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state conformation of anti-human immunodeficiency virus type-1 agents: Crystal structures of three 3'-azido-3'-deoxythymidine analogs

Abstract: The crystal structures of three anti-HIV 3'-azido-3'-deoxynucleosides have been determined to gain conformational information for structure-activity studies. The compounds 3'-azido-3'-deoxythymidine (AZT), 3'-azido-2',3'-dideoxyuridine (CS-87), and 3'-azido-2',3'-dideoxy-5-ethyluridine (CS-85) are all active inhibitors of HIV-1 replication. X-ray diffraction data for all three compounds were measured at 165 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…After energy minimization of AZTTP with the enzyme site model, the 3Ј-azido moiety of AZTTP fitted nicely in the pocket, along with the hydrogen bonding to the NH group of Tyr 115, which may contribute to the enhanced binding affinity of this inhibitor. AZTTP is positioned in such a way that it can maintain Watson-Crick base pairing between A and T. Also, we have found that only the 3Ј-endo (north) conformation of AZTTP fits into the active site of the HIV-1 RT, while it has been known that 2Ј-endo (south) conformation of AZT is favored at the kinase phosphorylation level (2,39,40). The result suggests that AZT by its flexible nature may adopt the south conformation required for the initial phosphorylation and subsequently switch to a north conformation in the triphosphate state for better interaction with the active site of the HIV-1 RT.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…After energy minimization of AZTTP with the enzyme site model, the 3Ј-azido moiety of AZTTP fitted nicely in the pocket, along with the hydrogen bonding to the NH group of Tyr 115, which may contribute to the enhanced binding affinity of this inhibitor. AZTTP is positioned in such a way that it can maintain Watson-Crick base pairing between A and T. Also, we have found that only the 3Ј-endo (north) conformation of AZTTP fits into the active site of the HIV-1 RT, while it has been known that 2Ј-endo (south) conformation of AZT is favored at the kinase phosphorylation level (2,39,40). The result suggests that AZT by its flexible nature may adopt the south conformation required for the initial phosphorylation and subsequently switch to a north conformation in the triphosphate state for better interaction with the active site of the HIV-1 RT.…”
Section: Methodsmentioning
confidence: 87%
“…Both 3TC and FTC [(Ϫ)-␤-L-2Ј,3Ј-dideoxy-5-fluoro-3Ј-thiacytidine] show potent antiviral activity against HIV and hepatitis B virus, with favorable pharmacokinetic and toxicity profiles (20,43). Therefore, structural features and conformational preferences of the D and L enantiomers, as well as their interactions with the target enzymes, have been the critical issue to be studied (4,26,27,39,40,43).The activation of nucleoside RT inhibitors involves two major events: phosphorylation by kinases and the interaction of the deoxynucleoside triphosphate (dNTP) with the RT (14,30,35). The antiviral activity of 2Ј,3Ј-dideoxynucleosides is dependent on their phosphorylation by cellular kinases in the cytoplasm to the corresponding 5Ј-triphosphates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compound (II) has a value of 105.7 (5) ° for this angle, indicating that the nitro group has considerable flexibility with respect to the ribose ring. Crystallographic studies of AZT itself and various 3'-azido-3'-deoxythymidine analogs (Birnbaum, Giziewicz, Gabe, Lin & Prusoff, 1987;Camerman, Mastropaolo & Camerman, 1987;Van Roey et al, 1988) have shown that the 3'-azido group prefers to adopt a trans conformation with respect to the C2'--C3' bond. For example, the C2'---C3'~N3'A--N3'B torsion angle in the two independent molecules in the crystal structure of AZT itself has values of 178 and 176 ° .…”
Section: Commentmentioning
confidence: 99%
“…For example, the C2'---C3'~N3'A--N3'B torsion angle in the two independent molecules in the crystal structure of AZT itself has values of 178 and 176 ° . The crystal structures of AZT itself (Birnbaum, Giziewicz, Gabe, Lin & Prusoff, 1987;Camerman, Mastropaolo & Camerman, 1987;Van Roey et al, 1988) show that the deoxyribose sugar pucker preference is in the C2'-endo or the closely related C3'-exo domain, which have pseudorotation phase angles in the range 170-220 °. Similar puckers have been observed in other nucleoside analogues with anti-HIV activity, leading to the hypothesis (Van Roey, Salerno, Chu & Schinazi, 1989;Taylor, Van Roey, Schinazi & Chu, 1990) that C2'-endo/C3'-exo types of sugar conformational preference are important for antiviral activity.…”
Section: Commentmentioning
confidence: 99%